The Effectiveness of a Foundation Year 1 Doctor Preparation Course for Final Year Medical Students. (January 2021) - Beedham, William; Wanigasooriya, Kasun; Layton, Georgia R; Taing Chan, Ley; Darr, Adnan; Mittapalli, Devender
Background: Starting work as a junior doctor can be daunting for any medical student. There are numerous aspects of the hidden curriculum which many students fail to acquire during their training. Objectives: To evaluate the effectiveness of a novel foundation year one (FY1) doctor preparation course focusing on certain core topics, practical tips and components of the hidden curriculum. The primary objective was to improve the confidence level and knowledge of final year medical students transitioning to FY1 doctors. Method: A 2-day, practical course titled 'Preparation 2 Practice' delivering hands-on, small-group and lecture-based teaching, covering core medical student undergraduate curriculum topics in medicine and surgery. The course content spanned therapeutics, documentation skills and managing acute clinical tasks encountered by FY1 doctors during an on-call shift. A pre- and post-course survey and knowledge assessment were carried out to assess the effectiveness of the course. The assessment was MCQ-based, derived from topics covered within our course. The 20-question test and a short survey were administered electronically. Results: Twenty students from a single UK medical school attended the course. 100% participation was observed in the pre- and post-course test and survey. The median post-course test result was 22 (IQR 20.25-23.75) which was higher than the median pre-course test score of 18.75 (IQR 17-21.75). A Wilcoxon sign rank test revealed a statistically significant difference between the pre- and post-course test results ( P  = .0003). The self-reported confidence score of delegates on starting work as a junior doctor was also significantly higher following the course ( P  = .004). Conclusion: The results show a significant improvement in perceived confidence and knowledge on core curriculum topics amongst final year medical students having attended our FY1 doctor preparation course. We conclude that there is scope for similar supplementary courses as an adjunct to the undergraduate medical curriculum.